The Teaching Method of Imam Badr al-Din al-Aini on Hadith through His Commentary on Sahih al-Bukhari | تعليمية الحديث النبوي عند الإمام بدر الدين العيني من خلال شرحه على صحيح البخاري - Chettih Benyoucef (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2020)
No one believes that the Western nations have done anything respectable in the field of teaching materials. It should not be denied. This is what is imposed on us by the objective scientific logic, but it is wrong and unfair to deny what is in our linguistic, literary and legal heritage from the seeds of their early position on education, teaching methods, Of the researchers prospecting and directing them to the people. It is among those who excelled in explaining the hadiths of the Prophet peace be upon him Imam Badr al-Din al-'Eini, where his explanation and the analysis of Al-Wafi is considered a model for the consolidation of the modern Hadith through the explanation of the encyclopedia on Saheeh Al-Bukhari and tagged as